The Challenge of Arctic shipping : science, environmental assessment, and human values - VanderZwaag, David L. (McGill-Queen's native and northern series, 1990)
This survey of the problems and challenges of shipping in the Arctic Ocean includes polar oceanography, marine mammals and ice-breakers, seabirds, petroleum exploration, oil spills, environmental impact of industrial activities, Inuit land claims and the possibility of native self-government.